Gedruk, Estetika Dalam Campursari - Bayu Aji, Nur Seto; Setiawan, Aris (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2025)
This study explores the aesthetics of gedruk music, focusing on the tonal blend of bonang, kempul, and saron within campursari. The integration of gedruk reflects the cultural dynamics of an evolving society, enriching the music while offering a fresh identity that revitalizes local culture. In campursari performances, gedruk creates a new spatial and temporal form, opening unique musical horizons. Using a descriptive qualitative method with a phenomenological approach, this study examines how gedruk emerges and transforms campursari. The sounds and rhythms of gedruk produce a distinct aesthetic that enriches the genre. Data collection includes document and video analysis of campursari performances featuring gedruk, alongside direct observations and interviews with performers and groups. Aesthetic analysis aims to understand how folk art adapts into popular music, focusing on rhythm, harmony, expression, and contextual elements. The study finds gedruk introduces a fresh aesthetic to campursari, blending traditional elements into popular music. This fusion simplifies complex tonal structures, reducing monotony for performers. Psychologically, this simplicity creates a fresh atmosphere and enhances enthusiasm among performers and audiences, demonstrating how folk elements like gedruk can redefine and enrich modern campursari music.